The Effectiveness of Online Coaching through Social Networking Site: A case study of Coach Potato Indonesia - Siti Mahdaria; Titus Angga Restuaji (Hasanuddin University, 2021)
In the more globalized world, social networking sites are used to connect people and popular as a learning platform. More people use webinars to talk about specific topics through a social network. The number of online courses raise and change the way people learn. People used to study in a classroom with a tutor in front of them, but now people only need to sit in front of a screen to learn new things. However, the effectiveness of this process is still questioned. Therefore, this study aims to analyse the effectiveness of online coaching through a social networking site and the critical challenge in online coaching and approach to tackle it. This study is qualitative research. The data is collected from online interviews with a semi-structured interview guide. The sample of the study is 12 mentees and 5 mentors who had been involved in 12 weeks of online scholarship coaching held by Coach Potato Indonesia. The data is analyzed using a thematic content method, and the effectiveness of online coaching is measured by using the Kirkpatrick Model. The result of the study is that online mentoring through social networking sites is effective and efficient, especially in particular related to geographical and financial issues. The authors found the critical challenges in online mentoring are internet connection and timing. Therefore, online mentoring should use multiple platforms to adjust with the technical issue that might occur.